The substitution account: the problem, the techniques and the politics - S. MICOSSI; F. SACCOMANNI (PSL Quarterly Review, 2013)
The present paper argues that in a longer-term perspective many of the problems and difficulties which caused the Substitution Account (SA) project to be scrapped are not as compelling as they previously appeared to be. The authors first review the purposes of the SA before looking at its main technical features. The reasons which prevented an agreement from being reached in Hamburg are then considered. The potential usefulness of a substitution scheme is then assessed agains the prospect of persisting payments imbalances in the world economy and of an emerging multi-currency reserve system.